Analisis Media Pembelajaran terhadap Pemahaman Peserta didik dalam Proses Pembelajaran di MA Plus Nurul Islam Sekarbela - Ratih Lestari; Dedi Riyan Rizaldi; Muhammad Fahrurrozi; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2024)
This study aims to analyze the use of learning media in improving student understanding at MA Plus Nurul Islam Sekarbela. The background of this research focuses on educational challenges in the era of globalization and technological development, which affect the way of delivering material through learning media. The research method used is qualitative descriptive with data collection techniques through observation and interviews with teachers and students. The results of the study show that although interactive learning media provides benefits, such as increasing students' interest and attention, most students prefer conventional learning using package books. Therefore, it is recommended to continue to develop a variety of learning media that can be adjusted to the needs and preferences of students to increase the effectiveness of the teaching and learning process in the future